New Books On Women, Gender & Feminism, no. 50, Spring 2007 - (:unkn) unknown (My University, 2017)
Bibliography. ISSN 1941-7241, 81p.
This bibliography represents a selection of new books (generally fifty or more pages long) and periodicals that have come to our attention primarily from reviews and publishers’ announcements and catalogs. For each title, we include all bibliographic information readily available to us.
Keywords: Feminism; Gender; New Books; Bibliography